Optimizing social-ecological analysis of coupled human-river systems through the integration of conceptual frameworks: the case of the Savegre watershed, Costa Rica - Espinoza-Cisneros, Edgar (2018)
Social-ecological systems, given their immanent complexity and unpredictability, pose intricate management challenges. Conceptual/analytical frameworks that more holistically integrate coupled social and natural systems and their basic interdependencies and interactions can significantly improve management and research efforts at multiple levels, specifically by accounting for the complex, multi-scalar processes involved, including the dynamics of distal and more proximate causal factors, as well as how they manifest and evolve in space and time. This paper presents a synthesis from a social-ecological analysis of the Savegre river watershed in Costa Rica, a recently designated UNESCO Biosphere Reserve. Through this exercise, the watershed is conceptualized as a coupled social-ecological system, with complex interconnections among social, ecological and physical components, for developing research agendas or specific normative efforts. Syntheses like the one presented here are particularly useful for more in-depth explorations of social-ecological issues, especially collective action problems derived from human-environment interactions at various scales. More effective formal and informal normative solutions to pressing sustainability dilemmas can also be envisioned through similar exercises.